Strained GaAs/InGaAs Core-Shell Nanowires for Photovoltaic Applications - Moratis, K. (Nanoscale Res Lett, 2016)
We report on the successful growth of strained core-shell GaAs/InGaAs nanowires on Si (111) substrates by molecular beam epitaxy. The as-grown nanowires have a density in the order of 10(8) cm(−2), length between 3 and 3.5 μm, and diameter between 60 and 160 nm, depending on the shell growth duration. By applying a range of characterization techniques, we conclude that the In incorporation in the nanowires is on average significantly smaller than what is nominally expected based on two-dimensional growth calibrations and exhibits a gradient along the nanowire axis. On the other hand, the observation of sharp dot-like emission features in the micro-photoluminescence spectra of single nanowires in the 900–1000-nm spectral range highlights the co-existence of In-rich enclosures with In content locally exceeding 30 %.